Balinese Students Pronunciation in Learning English: A Case Study of Sixth-Grade Students at SDN 1 Petulu Ubud - Suantari, Ni Kadek; Suastra, I Made; Aryani, I Gusti Agung Istri (Humanis, 2021)
This study is aimed to identify how the Balinese students pronounce English consonants and to analyse the factors that influenced the Balinese student’s pronunciation in pronouncing English consonants. This study was conducted as field research and the data was collected from the Balinese student’s pronunciation by recording their voices in pronouncing the target phonemes. Besides, interviewing was also done to know the factors that influence them in pronouncing the target phonemes. Data of this research was descriptively analysed by using qualitative methods and analysed by the theory proposed by Roach, Brown, and Harmer. The consonants chosen were the consonants that mostly do not occur in their native language structure such as /f/, /?/, /?/, /?/, /v/, /ð/, /z/, /?/, /?/ and the chosen English consonants that are pronounced differently from what it has written is /k/. The Balinese students were not familiar with those phonemes caused they found difficulties when they pronounced those phonemes sound. Foreign language pronunciation of the students was influenced by some factors: Age, First language interference, Learner differences (student’s aptitude and intelligence), and Motivation (teacher and other students).